2019
DOI: 10.1044/2018_lshss-18-0057
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Individuals With Disabilities Education Act Part B Procedural Safeguards: An Update

Abstract: Purpose The purpose of this study was to analyze the readability of Individuals with Disabilities Education Act (IDEA) Part B procedural safeguard documents, as distributed by each of the 50 U.S. states. Results were compared to the 5th- to 6th-grade readability guideline for documents recommended by experts in health literacy and health communication. Method A commercially available readability software, Readability Studio ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, the language used in the assessment tools can also lead to patients providing unreliable and confusing information, which does not always reflect their true experience. The readability of the questionnaires, therefore, is also an important confounding factor that should be considered when analysing this type of information Gray, Zraick, and Atcherson 2019;Douglas and Kelly-Campbell 2018). The term "ototoxicity" must be defined when publishing trials and research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the language used in the assessment tools can also lead to patients providing unreliable and confusing information, which does not always reflect their true experience. The readability of the questionnaires, therefore, is also an important confounding factor that should be considered when analysing this type of information Gray, Zraick, and Atcherson 2019;Douglas and Kelly-Campbell 2018). The term "ototoxicity" must be defined when publishing trials and research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hanish et al (2022) similarly note approximately 21% of U.S. adults read at, or below a 5 th -grade level, while an additional 30% read at a level between 6 th and 8 th grade. Readability, in the context of written materials, refers to the ease with which individuals can read and comprehend content (Gray et al, 2019). Predictors of readability encompass both the complexity of the document itself and the educational background of the reader.…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…In forming simple meaningful phrases , words at recommended 6th to 8th grade reading levels facilitate OADWS’s understanding of both verbal and written communication (Foe & Larson, 2016; Gray et al, 2019). Older adults have reported that informed consent documents are too complicated to understand, so they may “pretend” to read the informed consent because they feel “ashamed” to ask for explanations (Bloswick & Skowron, 2019).…”
Section: Using Simple Meaningful Phrases: Practical Applicationmentioning
confidence: 99%